2008
DOI: 10.1111/j.1463-1318.2008.01512.x
|View full text |Cite
|
Sign up to set email alerts
|

Combination endo‐radiological colorectal stenting: a prospective 5‐year clinical evaluation

Abstract: Combination endoscopic/fluoroscopic colorectal stenting is effective and safe. It may be particularly useful in the stenting of more proximal colonic strictures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 16 publications
3
6
1
1
Order By: Relevance
“…Although migration of an uncovered stent (as was used in the dog of the present report) is less likely than with a covered stent, tumor ingrowth through uncovered stent gaps can result in reobstruction and a necessity for restenting. 10,18,23 Lastly, marked improvement in clinical signs was not noted until 7 weeks after stent placement in the dog of the present report. Owners should be prepared for the possibility that dogs with placement of a colorectal stent for palliation may need to continue oral administration of medications indefinitely, and clinical signs may show slow improvement until the proper combination of medications and colorectal patency is achieved.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Although migration of an uncovered stent (as was used in the dog of the present report) is less likely than with a covered stent, tumor ingrowth through uncovered stent gaps can result in reobstruction and a necessity for restenting. 10,18,23 Lastly, marked improvement in clinical signs was not noted until 7 weeks after stent placement in the dog of the present report. Owners should be prepared for the possibility that dogs with placement of a colorectal stent for palliation may need to continue oral administration of medications indefinitely, and clinical signs may show slow improvement until the proper combination of medications and colorectal patency is achieved.…”
Section: Discussioncontrasting
confidence: 48%
“…Potential long-term complications related to the stent may have included tumor ingrowth through stent gaps resulting in obstruction, migration, and stent fracture. 10,23 Second, as malignant transformation can occur with colorectal neoplasia, it is recommended that dogs with benign masses (such as was originally found in the dog of the present report) be evaluated periodically after stent placement with thoracic radiography, abdominal ultrasonography, and colonoscopy (including biopsy) to assess progression. 4,7,22 Colonoscopy is also useful in the assessment of tumor ingrowth.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…There have even been some reports suggesting that stent placement is more difficult to perform in the descending colon or splenic flexure than in the rectum or sigmoid colon. 4,11,21 In our study, similar difficulties were observed in cases of the stent placement using radiologic method alone: inability to pass the guidewire through the obstructive lesion due to tortuous, curved angulation of the sigmoid colon (n=2), and the difficult approach of the angiographic catheter into a lesion located in the transverse colon (n=1).…”
Section: Discussionsupporting
confidence: 70%
“…Vários estudos demonstram maior mortalidade pós-operatória em pacientes operados na urgência 10,26,27 . No presente estudo, não foi possível avaliar e comparar a mortalidade tardia nos dois grupos, pois muitos pacientes foram encaminhados para terapia complementar em serviços de referência e perderam seguimento no HU-USP.…”
Section: Discussionunclassified